Evaluation of genetic risk loci for intracranial aneurysms in sporadic arteriovenous malformations of the brain. Issue 5 (21st July 2014) - Kremer, P H C; Koeleman, B P C; Pawlikowska, L; Weinsheimer, S; Bendjilali, N; Sidney, S; Zaroff, J G; Rinkel, G J E; van den Berg, L H; Ruigrok, Y M; de Kort, G A P; Veldink, J H; et al.
Abstract : Background: In genome-wide association studies (GWAS) five putative risk loci are associated with intracranial aneurysm. As brain arteriovenous malformations (AVM) and intracranial aneurysms are both intracranial vascular diseases and AVMs often have associated aneurysms, we investigated whether these loci are also associated with sporadic brain AVM. Methods: We included 506 patients (168 Dutch, 338 American) and 1548 controls, all Caucasians. Controls had been recruited as part of previous GWAS. Dutch patients were genotyped by KASPar assay and US patients by Affymetrix SNP 6.0 array. Associations in each cohort were tested by univariable logistic regression modelling, with subgroup analysis in 205 American cases with aneurysm data. Meta-analysis was performed by a Mantel-Haenszel fixed-effect method. Results: In the Dutch cohort none of the single nucleotide polymorphisms (SNPs) were associated with AVMs. In the American cohort, genotyped SNPs near SOX-17 (OR 0.74; 95% CI 0.56–0.98), RBBP8 (OR 0.76; 95% CI 0.62–0.94) and an imputed SNP near CDKN2B-AS1 (OR 0.79; 95% CI 0.64–0.98) were significantly associated with AVM. The association with SNPs near SOX-17 and CDKN2B-AS1 but not RBBP8 were strongest in patients with AVM with associated aneurysms. In the meta-analysis we found no significant associations between allele frequencies and AVM occurrence, but rs9298506, near SOX-17 approached statistical significance (OR 0.77; 95% CI 0.57–1.03, p=0.08). Conclusions: Our meta-analysis of two Caucasian cohorts did not show an association between five aneurysm-associated loci and sporadic brain AVM. Possible involvement of SOX-17 and RBBP8, genes involved in cell cycle progression, deserves further investigation.